Reconstruction of Financial Reports in Accordance with EMKM SAK (Case Study on Kopi Dako Julie Sukosari, Bondowoso Regency) - Bahtiar Adi Darmawan; Norita Citra Yuliarti; Rendy Mirwan Aspirandi (Finance : International Journal of Management Finance, 2025)
This study aims to reconstruct the financial statements of the Kopi Dako Julie MSME in Sukosari, Bondowoso Regency to comply with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) set by the Indonesian Institute of Accountants. The MSME has so far only recorded its finances manually and simply, without preparing formal financial statements such as financial position statements, profit and loss statements, and notes to the financial statements. The research method used is a case study with a qualitative descriptive approach. Primary data were obtained through interviews and direct observation, while secondary data were in the form of MSME financial recording documents. The results of the study indicate that after the reconstruction, the financial statements can be prepared completely in accordance with the SAK EMKM structure. The resulting report provides more accurate and relevant information, including net profit after tax of IDR 23,016,865 from total sales of IDR 331,000,000, with a net profit margin of 6.96%. This study emphasizes the importance of preparing financial statements that comply with standards to improve accountability, access to financing, and managerial decision making in MSMEs.